2023
DOI: 10.1029/2022jd037383
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Aerosol Properties and Ice‐Nucleating Particle Concentrations in Beijing

Abstract: Ice-nucleating particles (INPs) are required for the formation of primary ice at temperatures between −38°C and 0°C in the atmosphere. Observations have shown that dust particles can promote ice formation and lead to glaciation of midlevel clouds (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
0
0
Order By: Relevance
“…Zhang's research also confirmed the negligible influence of anthropogenic black carbon and secondary aerosols emissions on INP concentrations [54]. However, Ren's results showed that the INP concentrations gradually increased as aerosol conditions transitioned from clean to heavy pollution [55]. Therefore, further investigations are still required to understand the INPs sources and its influencing factors in China.…”
Section: Introductionmentioning
confidence: 88%
“…Zhang's research also confirmed the negligible influence of anthropogenic black carbon and secondary aerosols emissions on INP concentrations [54]. However, Ren's results showed that the INP concentrations gradually increased as aerosol conditions transitioned from clean to heavy pollution [55]. Therefore, further investigations are still required to understand the INPs sources and its influencing factors in China.…”
Section: Introductionmentioning
confidence: 88%